The Sociodigital Walkthrough: Studying the Nexus Between Social Characteristics and Material Technicalities on a Healthcare Application - Amato, Francesco; Aragona, Biagio; De Angelis, Mattia (Italian Sociological Review, 2024)
The walkthrough method originated from the field of software development but may be employed in several social research designs. However, its applications in the social sciences still need to be developed and consolidated. This article presents an application of the walkthrough method, called the Sociodigital walkthrough (SDW), to the study of human-machine interaction (HMI) within the Campania in Salute smartphone application, which provides all public healthcare services in the Campania region of Italy. We argue that this method allows the researcher to engage with the materiality of technology. Furthermore, it is relevant for analysing the interaction between the individual and the digital environment. The Sociodigital walkthrough could be employed for other exploratory studies on digital platforms and prove interesting if used in digital research designs.